2010
DOI: 10.1371/journal.pone.0008604
|View full text |Cite
|
Sign up to set email alerts
|

Co-Inhibition of BCL-W and BCL2 Restores Antiestrogen Sensitivity through BECN1 and Promotes an Autophagy-Associated Necrosis

Abstract: BCL2 family members affect cell fate decisions in breast cancer but the role of BCL-W (BCL2L2) is unknown. We now show the integrated roles of the antiapoptotic BCL-W and BCL2 in affecting responsiveness to the antiestrogen ICI 182,780 (ICI; Fulvestrant Faslodex), using both molecular (siRNA; shRNA) and pharmacologic (YC137) approaches in three breast cancer variants; MCF-7/LCC1 (ICI sensitive), MCF-7/LCC9 (ICI resistant), and LY2 (ICI resistant). YC137 inhibits BCL-W and BCL2 and restores ICI sensitivity in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 44 publications
(51 reference statements)
4
68
0
Order By: Relevance
“…LCC9 cells have been shown to express higher basal levels of Bcl-2 relative to parental MCF-7 cells, and RNA interference (RNAi) for Bcl-2 induces an autophagic response in these cells (32). We previously reported that Bcl-2 is regulated in response to E2 (33) and consistent with this, E2 strongly induced Bcl-2 expression in MCF-7 cells (Fig.…”
Section: Effects Of Erb Agonists On Cell-cycle Proteinssupporting
confidence: 56%
“…LCC9 cells have been shown to express higher basal levels of Bcl-2 relative to parental MCF-7 cells, and RNA interference (RNAi) for Bcl-2 induces an autophagic response in these cells (32). We previously reported that Bcl-2 is regulated in response to E2 (33) and consistent with this, E2 strongly induced Bcl-2 expression in MCF-7 cells (Fig.…”
Section: Effects Of Erb Agonists On Cell-cycle Proteinssupporting
confidence: 56%
“…From the perspective of XBP1, proposed connections with BCL2 and NF-kB would be present only with estrogens and lost with the addition of Fulvestrant. BCL2 is a key determinant for maintaining cell survival with the UPR (28), and we now know that BCL2 is overexpressed in antiestrogen resistant cells that also overexpress the endogenous XBP1(s) (52). Estrogenic induction of BCL2 is well known, and we have shown that XBP1 is also a likely regulator of BCL2, which is overexpressed in cells that have been transfected with XBP1 (33).…”
Section: Initial Representation Of Xbp1-associated Signalingmentioning
confidence: 88%
“…We have recently shown that the full effect of the small molecule BCL2 inhibitors is mimicked only when both BCL2 and BCLW are coinhibited (52). Other interactions also occur but these are not directly reflected in this model.…”
Section: Initial Representation Of Xbp1-associated Signalingmentioning
confidence: 89%
See 2 more Smart Citations